Primary retroperitoneal filariasis: a common disease of tropics with uncommon presentation and review of literature - Diwakar, Deepak Kumar (BMJ Case Rep, 2018)
Lymphatic filariasis is caused by nematode filariae Wuchereria bancrofti, Brugia malayi or Brugia timori. It is commonly seen in tropical and subtropical regions of the world and affects the lymphatic system of humans, who are the definitive host while mosquito is the intermediate host. The most common manifestation of the disease is hydrocele followed by lower limb lymphoedema and elephantiasis. Although filariasis is much more common entity in north India, its presentation as retroperitoneal cyst is very rare with reported incidence rate of 1/105 000. We present a case of primary retroperitoneal filariasis in a 52-year-old man, without any classic signsandsymptoms, diagnosed postoperatively after surgical resection following diagnostic uncertaintyandfailure of other medical therapies.